Analisis Faktor-Faktor yang Mempengaruhi Minat Membaca di Kalangan Mahasiswa Pelatih Olahraga pada Era Transformasi Digital: Studi Deskriptif Kuantitatif : Faktor-faktor yang Mempengaruhi Minat Membaca di Kalangan Mahasiswa Pelatih Olahraga - Syifa Kamila, Salwa (UNIB Press, 2025)
This study aims to investigate the reading preferences of students of Sports Coaching Education Study Program Batch 2023, Faculty of Sports Science, Universitas Negeri Semarang. Reading is an activity that is sometimes neglected in the era of technological advancement, despite the fact that reading is very important for the development of knowledge and critical thinking skills (literacy). This research uses a quantitative design, with a descriptive type of research design. The data collection method uses a survey in the form of a questionnaire made through google form. The sample of this research is the 2023 students of the Sports Coaching Education Study Program, Faculty of Sports Science, Semarang State University. The research results are detailed according to the components or indicators of the test instrument (can be in the form of numbers and %). It shows that various factors, including time management, access to reading materials, and academic environment, have an impact on students' reading interest. The conclusion of this study suggests that in order to enhance intellectual capacity and facilitate learning, students should build good reading habits.